University Reputation And Quality Of Lecturers For The Decision Of Choosing Which Mediated Promotion - Azizah Novita; Elfitra Desy Surya; Nur Afrina (Yayasan Multidimensi Kreatif, 2024)
This study examines the influence of campus reputation on promotion and voting decisions at Sekolah Tinggi Agama Islam Darul Arafah Deli Serdang. In the context of intense competition between universities, campus reputation is crucial in attracting prospective students. Parents are identified as key stakeholders who can have a significant impact on the campus's reputation. This study aims to test and analyze the influence of campus reputation and lecturer quality on choice decisions mediated by promotion. The data was analyzed using the SEM-PLS path analysis method with a sample of 227 people. This research shows that the reputation of the campus has a positive and significant effect on the decision to choose Darul Arafah Islamic College Deli Serdang. In addition, promotion has a positive and significant effect on the decision to choose students. The reputation of the campus and the quality of lecturers have a positive and significant influence on the decision to choose a promotion-mediated choice. The results of this study provide deep insight for the high school in managing reputation and improving promotional strategies to attract prospective students. Recommendations include increased transparency of lecturer information and innovative learning approaches, optimization of the school's website, strengthening relationships with alumni and staff, and further emphasis on developing the quality of lecturers. Thus, this research has important implications in the development of higher education at Sekolah Tinggi Agama Islam Darul Arafah Deli Serdang (STAI-DA).